2004
DOI: 10.1107/s1600536804020161
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-1-[bis(N,N-dimethylamino)phosphoramido]benzimidazole

Abstract: The crystal structure of the title compound, C11H18N5OP, is stabilized by an intermolecular N—H⋯N‐type hydrogen bond and another C—H⋯O interaction that is intramol­ecular. The N—H⋯N hydrogen bonding leads to inversion‐related dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…This event provides solid observational evidence that recurrent two-sided loop jets can be driven by minifilament eruptions, which is in line with previous observations that minifilament eruptions result in single-spire jets (Sterling et al 2015Raouafi et al 2016). This is inconsistent with previous classical two-sided loop jet model (Yokoyama & Shibata 1995 and observations (Alexander & Fletcher 1999;Jiang et al 2013;Zheng et al 2018), which thought two-sided loop jet is driven by magnetic reconnection between emerging bipoles and their overlying horizontal magnetic fields.…”
Section: Conclusion and Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This event provides solid observational evidence that recurrent two-sided loop jets can be driven by minifilament eruptions, which is in line with previous observations that minifilament eruptions result in single-spire jets (Sterling et al 2015Raouafi et al 2016). This is inconsistent with previous classical two-sided loop jet model (Yokoyama & Shibata 1995 and observations (Alexander & Fletcher 1999;Jiang et al 2013;Zheng et al 2018), which thought two-sided loop jet is driven by magnetic reconnection between emerging bipoles and their overlying horizontal magnetic fields.…”
Section: Conclusion and Discussionsupporting
confidence: 67%
“…It is generally accepted that omnipresent jet activities of various spatial and temporal scales in the solar atmosphere are caused by magnetic reconnection between emerging magnetic flux and pre-existing ambient coronal magnetic fields (Shibata et al 1992(Shibata et al , 1994Shimojo et al 1996;Jiang et al 2007;Pariat et al 2010;Yang et al 2011;Li et al 2012;Raouafi et al 2016). Shibata et al (1994) suggested that when a bipolar emerging flux emerges from below the solar surface into the corona and interacts with a vertical or oblique coronal field, an anemone jet will be initiated; and when a bipolar emerging flux intrudes into and continuously interacts with a horizontal coronal field, a twosided loop jet will be initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding author: Yuandeng Shen ydshen@ynao.ac.cn Jet or jet-like phenomena are widely observed in the solar atmosphere; they are thought to be important for understanding the enigmatic problems of coronal heating and the acceleration of solar winds (Raouafi et al 2016). Based on morphology, solar jets are divided into collimated anemone jets and two-sided-loop jets, in which the former is produced by the magnetic reconnection between emerging bipoles and the ambient open magnetic fields (Yokoyama & Shibata 1995;Shen et al 2011), while the latter is by the reconnection between emerging bipoles and the overlying horizontal fields (Yokoyama & Shibata 1995;Tian et al 2017;Miao et al 2018;Sterling et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations indicate that solar jets are commonly associated with magnetic flux emergence, cancellation, and micro-flares at their eruption source region (Jiang et al 2007;Panesar et al 2017;Sterling et al 2018). Statistical studies show that solar jets have a speed of about 200 km s −1 , widths in the range of 2000-200000 km, and lifetimes from minutes to tens of minutes (Nisticò et al 2009;Shen et al 2011;Pucci et al 2013;Raouafi et al 2016). Studies in the past few decades have indicated that jet phenomenon is very important for our understanding of solar physics.…”
mentioning
confidence: 98%